Different Associations of Systolic Blood Pressure and Body Mass Index With Cardiac Structure and Function in Young Children. Issue 11 (31st August 2022) - Wu, Yujian; Li, Zhuoyan; Du, Bowen; Ye, Yujiao; Wang, Hualin; Niu, Yiwei; Chen, Sun; Wu, Yurong; Jin, Hong; Zhang, Xi; Wang, Jian; Sun, Kun
Abstract : Background: Both elevated systolic blood pressure (SBP) and excess weight can lead to early cardiovascular organ damage in children. In this study, we investigated whether there is a difference in the associations of SBP and body mass index (BMI) with cardiovascular structure and function in 4-year-old children. Methods: In 1474 children (52.3% males) from the Shanghai Birth Cohort, physical examination and echocardiography were performed. Standardized linear regression models were used to evaluate the associations of BMI Z score and SBP Z score with cardiovascular parameters and to compare the strengths of these associations. Results: The incidence of SBP elevation significantly increased in overweight children. SBP was positively related to heart rate, left ventricular (LV) ejection fraction and fraction shortening (β=1.824 [95% CI, 1.014–2.634], 0.579 [0.294–0.864], and 0.480 [0.257–0.704], respectively). BMI Z score was positively associated with LV mass index (β=1.225 [0.863–1.587]) and the risk of LV hypertrophy (odds ratio=1.428 [1.157–1.761]) but negatively related to measures of systolic function, including LV ejection fraction, LV fraction short, and global longitudinal strain (β=−0.417 [−0.735 to −0.099], −0.302 [−0.551 to −0.053], and −0.392 [−0.621 to −0.163], respectively). No noteworthy additive or multiplicative interactions between BMI and SBP were detected. Conclusions: Elevations in both BMI and SBP were related to cardiac structure and function in children as young as 4 years old. Elevated SBP was associated with increased heart rate and LV ejection at the early stage of BP elevation. BMI showed a closer relationship with left heart diameters and geometry than SBP.